International expert opinion on the management of infection caused by azole-resistant Aspergillus fumigatus. (July 2015) - Verweij, Paul E.; Ananda-Rajah, Michelle; Andes, David; Arendrup, Maiken C.; Brüggemann, Roger J.; Chowdhary, Anuradha; Cornely, Oliver A.; Denning, David W.; Groll, Andreas H.; Izumikawa, Koichi; Kullberg, Bart Jan; Lagrou, Katrien; et al.
Abstract: An international expert panel was convened to deliberate the management of azole-resistant aspergillosis. In culture-positive cases, in vitro susceptibility testing should always be performed if antifungal therapy is intended. Different patterns of resistance are seen, with multi-azole and pan-azole resistance more common than resistance to a single triazole. In confirmed invasive pulmonary aspergillosis due to an azole-resistant Aspergillus, the experts recommended a switch from voriconazole to liposomal amphotericin B (L-AmB; Ambisome ® ). In regions with environmental resistance rates of ≥10%, a voriconazole–echinocandin combination or L-AmB were favoured as initial therapy. All experts recommended L-AmB as core therapy for central nervous system aspergillosis suspected to be due to an azole-resistant Aspergillus, and considered the addition of a second agent with the majority favouring flucytosine. Intravenous therapy with either micafungin or L-AmB given as either intermittent or continuous therapy was recommended for chronic pulmonary aspergillosis due to a pan-azole-resistant Aspergillus . Local and national surveillance with identification of clinical and environmental resistance patterns, rapid diagnostics, better quality clinical outcome data, and a greater understanding of the factors driving or minimising environmental resistance are areas where research is urgently needed, as well as the development of new oral agents outside the azole drug class.